Answer:
x=-10
Step-by-step explanation:
2(x+3)=x-4
2*x+2*3=x-4
2x+6=x-4
2x-x=-4-6
x=-10
Answer:
![\vec{BC}=2b - 4a](https://tex.z-dn.net/?f=%20%5Cvec%7BBC%7D%3D2b%20-%204a%3C%2Fp%3E%3Cp%3E)
![\vec{XY}=a+ b](https://tex.z-dn.net/?f=%20%5Cvec%7BXY%7D%3Da%2B%20b%20)
![\vec {CY}=a - 2b](https://tex.z-dn.net/?f=%5Cvec%20%7BCY%7D%3Da%20-%202b)
Step-by-step explanation:
By the triangular law of vector addition:
![\vec {CY}=\vec {CA}+ \vec{AY}](https://tex.z-dn.net/?f=%5Cvec%20%7BCY%7D%3D%5Cvec%20%7BCA%7D%2B%20%5Cvec%7BAY%7D)
![\vec {CY}=a - 2b](https://tex.z-dn.net/?f=%5Cvec%20%7BCY%7D%3Da%20-%202b)
We have that;
![\frac{YB}{AY} = \frac{3}{1}](https://tex.z-dn.net/?f=%5Cfrac%7BYB%7D%7BAY%7D%20%3D%20%20%5Cfrac%7B3%7D%7B1%7D%20)
![\implies YB = 3 AY \\ \vec {YB} = 3 \vec {AY}](https://tex.z-dn.net/?f=%20%5Cimplies%20YB%20%3D%203%20AY%20%5C%5C%20%20%5Cvec%20%7BYB%7D%20%20%3D%203%20%20%5Cvec%20%7BAY%7D%20)
![\vec {YB} = 3 a](https://tex.z-dn.net/?f=%5Cvec%20%7BYB%7D%20%20%3D%203%20a)
From triangle ABC,
![\vec{BC}=\vec{BA}+\vec{AC} \\ \vec{BC}=2b - 4a](https://tex.z-dn.net/?f=%5Cvec%7BBC%7D%3D%5Cvec%7BBA%7D%2B%5Cvec%7BAC%7D%3C%2Fp%3E%3Cp%3E%20%5C%5C%20%5Cvec%7BBC%7D%3D2b%20-%204a%3C%2Fp%3E%3Cp%3E)
Again from triangle XYB
![\vec{XY}=\vec{YB}+\vec{BX} \\](https://tex.z-dn.net/?f=%5Cvec%7BXY%7D%3D%5Cvec%7BYB%7D%2B%5Cvec%7BBX%7D%20%5C%5C%20)
![\vec{XY}=\vec{YB}+ \frac{1}{2} \vec{BC}](https://tex.z-dn.net/?f=%5Cvec%7BXY%7D%3D%5Cvec%7BYB%7D%2B%20%5Cfrac%7B1%7D%7B2%7D%20%5Cvec%7BBC%7D)
![\vec{XY}=3a+ \frac{1}{2} (2b - 4a)](https://tex.z-dn.net/?f=%5Cvec%7BXY%7D%3D3a%2B%20%5Cfrac%7B1%7D%7B2%7D%20%282b%20-%204a%29)
![\vec{XY}=3a+ b - 2a \\ \vec{XY}=a+ b](https://tex.z-dn.net/?f=%5Cvec%7BXY%7D%3D3a%2B%20b%20-%202a%20%5C%5C%20%5Cvec%7BXY%7D%3Da%2B%20b%20)
Answer:
y = (3/5)x+26/5 or 5y = 3x+26
Step-by-step explanation:
Applying,
The equation of a line in two point form
(y₂-y₁)/(x₂-x₁) = (y-y₁)/(x-x₁)............... Equation 1
From the question,
Given: y₂ = 7, y₁ = 4, x₂ = 3, x₁ = -2
Substitute these values into equation 1
(7-4)/[3-(-2)] = (y-4)/(x+2)
3/5 = (y-4)/(x+2)
5(y-4) = 3(x+2)
5y-20 = 3x+6
5y = 3x+6+20
5y = 3x+26
y = (3/5)x+26/5
Hence the equation of the line is y = (3/5)x+26/5 or 5y = 3x+26
Answer:
$8h
Your pay is $288 for working 36 hours
Step-by-step explanation:
I hope this helps :)
Write the first ratio as 11/100 and set it equal to 22/n.
since 11 x 2=22 you can multiply 100 x 2 and you'll get 200.
*Check*: 11% of 200=22